A biography of the pixel - Smith, Alvy Ray 1943- (Tantor Media, Inc., 2022)
The Great Digital Convergence of all media types into one universal digital medium occurred, with little fanfare, at the recent turn of the millennium. The bit became the universal medium, and the pixel conquered the world. Henceforward, nearly every picture in the world would be composed of pixels. In A Biography of the Pixel, Pixar cofounder Alvy Ray Smith argues that the pixel is the organizing principle of most modern media, and he presents a few simple but profound ideas that unify the dazzling varieties of digital image making. Smith's story of the pixel's development begins with Fourier waves, proceeds through Turing machines, and ends with the first digital movies from Pixar, DreamWorks, and Blue Sky. Today, almost all the pictures we encounter are digital. Smith explains, engagingly and accessibly, how pictures composed of invisible stuff become visible-that is, how digital pixels convert to analog display elements. Taking the special case of digital movies to represent all of Digital Light (his term for pictures constructed of pixels), and drawing on his decades of work in the field, Smith approaches his subject from multiple angles. A Biography of the Pixel is essential reading for anyone who has watched a video on a cell phone, played a videogame, or seen a movie.
Online resource; title from title details screen (O'Reilly, viewed May 3, 2022)
Keywords: Computer animation -- History; Animation par ordinateur; Histoire; Computer animation; Downloadable audio books; Audiobooks; History; Livres audio